HOUSEHOLD FOOD SECURITY DURING THE COVID-19 PANDEMIC IN THE NORTH SURABAYA REGION - Amalia Ruhana; Veni Indrawati; Choirul Anna Nur Afifah; Cleonara Yanuar Dini; Lini Anisfatus Sholihah (GEMA KESEHATAN, 2022)
The current COVID-19 pandemic has greatly affected all areas of human life, especially in the economic sector, which in turn will affect household consumption, and nutrition. The purpose of this study was to determine the status of family food security in the northern Surabaya area during the covid 19 pandemic, job changes, changes in family income and the efforts made to deal with changes in income. This research is a descriptive study with a cross-sectional study design. The population of this study is the entire population who live in the area of ​​North Surabaya. The research sample was calculated using the Slovin formula, a minimum sample of 100 samples, to anticipate dropouts, it was added to 120 samples which were then divided evenly into five sub-districts in the North Surabaya area, namely Semampir, Krembangan, Kenjeran, Bulak, and Pabean Cantian. Data collection on food security using the Household Food Insecurity Access Scale (HFIAS) instrument, data on changes in employment and family income using a questionnaire. Most of the respondents in North Surabaya are from food-insecure families (56.67%) and 20.83% of them are severe food insecure families. As many as 12.50% of the fathers in the respondent's families experienced a job change during this pandemic and more than half of the head of the family (56.67%) experienced a lower-income change. Most respondents try to deal with changes in income by making savings. Keywords: Food security, Household food security, Covid-19 pandemic